Change : social conflict or harmony? Results of a Stockholm Roundtable (UNDP New YorkUS, 1994)
Looks at several of the major problems that are afflicting virtually every country today and proposes solutions. These problems include poverty, unemployment and social disintegration.
Summary of a conference sponsored by the Swedish Government and UNDP